2019
DOI: 10.9734/ijpss/2019/v27i330075
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Carbon Stock across Different Forest Physiognomy in a Tropical Rainforest Ecosystem at Obafemi Awolowo University Ile-Ife, Nigeria

Abstract: This study investigated carbon stock in above-ground biomass across different physiognomies in Obafemi Awolowo University tropical rainforest ecosystem. This was with a view of increasing the understanding of carbon cycle in tropical rainforest in Nigeria. Two 20 m x 20 m plots were marked out in the secondary forest, Tectona grandis and Riparian vegetations. Total enumeration was carried out for the living tree, the Diameter at Breast Height (DBH) of trees ≥10 cm were measured at 1.3 m above the ground … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Nonetheless, this result is consistent with the findings of Pato et al (2017) who reported a higher total biomass in forest (12.85 Mg ha -1 ) than in orchard (5.38 Mg ha -1 ). The variation in tree biomass in this study may be linked to differences in site conditions, tree density, altitude, stand age, tree size class, rainfall pattern and soil conditions (Peichl et al, 2006;Terakunpisut et al, 2007;Gairola et al, 2011;Justine et al, 2015;Arubasa and Odiwe, 2019). The high values for AGB and BGB in the forest ecosystem are connected to the high density of trees with large girths while the low values for these variables in the orchard result from low density of trees having small DBH (Gibbs et al, 2007;Singh, 2014;Gautam and Mandal, 2016).…”
Section: Discussionmentioning
confidence: 80%
“…Nonetheless, this result is consistent with the findings of Pato et al (2017) who reported a higher total biomass in forest (12.85 Mg ha -1 ) than in orchard (5.38 Mg ha -1 ). The variation in tree biomass in this study may be linked to differences in site conditions, tree density, altitude, stand age, tree size class, rainfall pattern and soil conditions (Peichl et al, 2006;Terakunpisut et al, 2007;Gairola et al, 2011;Justine et al, 2015;Arubasa and Odiwe, 2019). The high values for AGB and BGB in the forest ecosystem are connected to the high density of trees with large girths while the low values for these variables in the orchard result from low density of trees having small DBH (Gibbs et al, 2007;Singh, 2014;Gautam and Mandal, 2016).…”
Section: Discussionmentioning
confidence: 80%